PENGARUH SOFT SKILLS SISWA MELALUI MOTIVASI BELAJAR TERHADAP KESIAPAN KERJA SISWA PADA PROGRAM STUDI MANAJEMEN PERKANTORAN DAN LAYANAN BISNIS SMK NEGERI 1 LAMONGAN - Rosyidah, Haniatur; Ibadil Maula, Farij (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The high open unemployment rate among graduates of Vocational High Schools (SMK), along with the increasingly competitive demands of the labor market, indicates that SMK graduates are required not only to possess hard skills but also soft skills supported by high learning motivation in order to achieve optimal job readiness. In line with this phenomenon, this study aims to analyze the effect of soft skills on the job readiness of students in the Office Management and Business Services Program (MPLB) at SMK Negeri 1 Lamongan, with learning motivation considered as an intervening variable. This study employed a quantitative approach with an explanatory research design. The sample consisted of 140 students selected through probability sampling using the proportionate stratified random sampling method from a population of 215 students Data were collected through questionnaires distributed via Google Forms and analyzed using Partial Least Squares-Structural Equation Modeling (PLS-SEM) with SmartPLS 4 software. The results indicate that soft skills have a positive and significant effect on job readiness, with a t-statistic value of 5.666 > 1.96 and a p-value of 0.000 < 0.05. Soft skills also have a positive and significant effect on learning motivation, with a t-statistic value of 12.239 > 1.96 and a p-value of 0.000 < 0.05. Furthermore, learning motivation has a positive and significant effect on job readiness, with a t-statistic value of 7.233 > 1.96 and a p-value of 0.000 < 0.05. In addition, learning motivation was found to significantly mediate the effect of soft skills on job readiness, with a t-statistic value of 6.786 > 1.96 and a p-value of 0.000 < 0.05. This study concludes that soft skills positively influence students’ job readiness through learning motivation as a mediating variable.